2003
DOI: 10.1242/jcs.00370
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of c-Myc and proteasomes at the nucleoli of cells containing elevated c-Myc protein levels

Abstract: c-Myc is a predominately nuclear transcription factor that is a substrate for rapid turnover by the proteasome system. Cancer-related mutations in c-Myc lead to defects in its degradation and thereby contribute to the increase in its cellular level that is associated with the disease. Little is known about the mechanisms that target c-Myc to the proteasomes. By using a GFP fusion protein and live analysis we show that c-Myc shuttles between the nucleus and cytoplasm and thus it could be degraded in either comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
66
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 49 publications
12
66
1
Order By: Relevance
“…There is the possibility that the effects of NPM on ribosomal biogenesis and other cellular processes are also influenced by interaction with c-Myc, because c-Myc has been shown to stimulate many cellular functions, including ribosomal biogenesis (2). c-Myc has also been found in the nucleolus under certain conditions (21,22), raising the possibility that they may cooperate in nucleolar functions.…”
Section: Discussionmentioning
confidence: 99%
“…There is the possibility that the effects of NPM on ribosomal biogenesis and other cellular processes are also influenced by interaction with c-Myc, because c-Myc has been shown to stimulate many cellular functions, including ribosomal biogenesis (2). c-Myc has also been found in the nucleolus under certain conditions (21,22), raising the possibility that they may cooperate in nucleolar functions.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that compartmentalization of nuclear proteins plays an important role in controlling key functions, including gene expression (34), ubiquitination (35), and protein degradation (36). The nuclear distribution pattern of c-Jun in the control cells resembles that of overexpressed transcription factor c-Myc, which is thought to be sequestered to the nucleolus for ubiquitination (37) and degradation by the proteasome (38). In HeLa cells, similar c-Jun-enriched inclusions have been shown to contain aggregates of poyubiquitinated protein and to co-localize with 20 S proteasomes (30), suggesting these structures are sites of protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolar sequestration has been reported to regulate protein activity (Tao and Levine, 1999;Visintin et al, 1999) One possibility is that PRIMA-1 MET affects ribosomal biogenesis by inducing accumulation of mutant p53 and other proteins in the nucleoli. Studies by Arabi et al (2003Arabi et al ( , 2005, have shown that excess c-Myc can accumulate within nucleoli and activate Pol I transcription in the absence of Pol II transcription, suggesting that c-Myc drives cell growth by stimulating ribosome biogenesis. In contrast, wild-type p53 can suppress Pol I transcription by directly interfering with the assembly of a protein complex that is essential for transcriptional initiation on the rRNA promoter (Zhai and Comai, 2000).…”
Section: Discussionmentioning
confidence: 99%